Genetic analysis of 17 Y-STR loci in Han and Korean populations from Jilin Province, Northeast China. (May 2016) - Han, Yinan; Li, Liming; Liu, Xiaoyang; Chen, Wenqing; Yang, Shuping; Wei, Lanhai; Xia, Mingying; Ma, Teng; Jin, Li; Li, Shilin
Highlights: We report haplotype frequencies on 17 Y-STR loci of the Chinese Han and Korean populations in Jilin Province. Jilin Han and Korean populations differed from each other significantly. Jilin Han showed no significant difference from almost any other Han population. Jilin Han showed significant differences from most other Chinese ethnic populations. Haplotype frequencies in the Jilin Korean showed significant differences from all reference populations. Abstract: In this study, 17 Y chromosomal short tandem repeats (Y-STRs) were analyzed in 302 male individuals from the Chinese Han and Korean populations of Jilin Province. The haplotype diversities of two populations reached 0.99969 and 0.99874, respectively. The Jilin Han and Korean populations differed from each other significantly. The Jilin Han population showed no significant difference from almost any other Han population, but it did show significant differences from most other Chinese ethnic populations. The haplotype frequencies in the Jilin Korean population studied here showed significant differences from all reference populations in earlier reports. These data provide a reference for the Y-STR database in Jilin Province, and they may be valuable for population genetic analysis.